2020
DOI: 10.3390/jcm9010226
|View full text |Cite
|
Sign up to set email alerts
|

Induction of HO-1 by Mevastatin Mediated via a Nox/ROS-Dependent c-Src/PDGFRα/PI3K/Akt/Nrf2/ARE Cascade Suppresses TNF-α-Induced Lung Inflammation

Abstract: Background: Mevastatin (MVS), a 3-hydroxy-3-methylglutaryl coenzyme, a reductase (HMG-CoA) inhibitor, has anti-inflammatory effects potentially via up-regulation of heme oxygenase-1 (HO-1). However, the mechanisms underlying MVS-induced HO-1 expression remain largely unknown in human pulmonary alveolar epithelial cells (HPAEpiCs). Methods: HO-1 and intercellular adhesion molecule (ICAM)-1 expression were determined using real-time PCR, Western blotting, and promoter reporter analyses. The signaling components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 50 publications
(88 reference statements)
1
20
0
Order By: Relevance
“…NAC and apocynin have prevented PI3K activation in several experimental systems [ 153 , 154 , 155 , 156 ]. NAC increases cellular synthesis of glutathione and can reduce superoxide generation [ 157 ].…”
Section: Resultsmentioning
confidence: 99%
“…NAC and apocynin have prevented PI3K activation in several experimental systems [ 153 , 154 , 155 , 156 ]. NAC increases cellular synthesis of glutathione and can reduce superoxide generation [ 157 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study shows that up-regulation of HO-1 protects against lung inflammatory responses induced by LPS [21]. In addition, MVS has been shown to time-dependently induce the expression of HO-1 expression in HPAEpiCs [23]. Here, we evaluated the effect of HO-1 expression by MVS on the TNF-α-induced VCAM-1 expression in HPAEpiCs.…”
Section: Up-regulation Of Ho-1 By Mvs Reduces the Tnfα-induced Vcam-1 Expressionmentioning
confidence: 92%
“…A previous study using the zymosan-injected air pouch to trigger inflammation found that pretreatment with atorvastatin attenuated cell influx and the expression of proinflammatory cytokines and chemokines along with induction of HO-1 in the cells of the exudate of the air pouch, effects which were reversed by exposure to tin protoporphyrin IX (SnPPIX), an heme oxygenase inhibitor. 217 Our recent study also revealed that HO-1 induction by mevastatin through the Nrf2/ARE axis was regulated by the p47 phox /Nox2/ROS-dependent activation of c-Src/PDGFR/PI3K/Akt 112 or by c-Jun activation activated by the PKC/Pyk2/p38 MAPK- or JNK1/2-dependent pathways and led to AP-1-binding on the HO-1 promoter region 113 using HPAEpiCs and animal studies. Further, mevastatin can suppress inflammatory responses mediated by TNFα.…”
Section: The Role Of Statins In Pulmonary Inflammatory Diseasesmentioning
confidence: 96%
“… 86 Our recent studies have demonstrated that HO-1 is induced by mevastatin mediated via a Nox/ROS-dependent c-Src/PDGFRα/PI3K/Akt/Nrf2/ARE cascade or via c-Jun activation of PKCα/Pyk2/p38α MAPK or JNK1/2 to suppress proinflammatory mediators-mediated inflammatory responses in human pulmonary alveolar epithelial cells (HPAEpiCs). 112 , 113 Carbon monoxide-releasing molecule (CORM-2) induces HO-1 expression via Src, epidermal growth factor receptor (EGFR), and PI3K/Akt to increase the formation of the Nrf2 and AREs complex in HPAEpiCs to suppress TNF-α-mediated inflammatory responses. 114 CORM-2 also activates a PYK2/PKCα/ERK1/2/AP-1 pathway leading to HO-1 expression in HPAEpiCs.…”
Section: Ho-1 Inducersmentioning
confidence: 99%
See 1 more Smart Citation